"We are everything to everyone": a systematic review of factors influencing the accountability relationships of Aboriginal and Torres Strait Islander health workers (AHWs) in the Australian health system - Stephanie M. Topp; Alexandra Edelman; Sean Taylor (BMC, 2018)
Abstract Background Health policy in Australia positions Aboriginal and Torres Strait Islander Health Workers (AHWs) as central to improving Aboriginal and Torres Strait Islander peoples' health, with high expectations of their contribution to closing the gap between Indigenous and non-Indigenous health outcomes. Understanding how AHWs' governance and accountability relationships influence their ability to address such health inequities has policy, programme and ethical significance. We sought to map the evidence of AHWs' experiences of accountability in the Australian health system. Methods We followed an adapted qualitative systematic review process to map evidence on accountability relations in the published literature. We sought empirical studies or first-person accounts describing AHWs' experiences of working in government or Aboriginal community-controlled services anywhere in Australia. Findings were organised according to van Belle and Mayhew's four dimensions of accountability - social, political, provider and organisational. Results Of 27 included studies, none had a primary focus on AHW governance or AHWs' accountability relationships. Nonetheless, selected articles provided some insight into AHWs' experiences of accountability across van Belle and Mayhew's four dimensions. In the social dimension, AHWs' sense of connection and belonging to community was reflected in the importance placed on AHWs' cultural brokerage and advocacy functions. But social and cultural obligations overlapped and sometimes clashed with organisational and provider-related accountabilities. AHWs described having to straddle cultural obligations (e.g. related to gender, age and kinship) alongside the expectations of non-Indigenous colleagues and supervisors which were underpinned by 'Western' models of clinical governance and management. Lack of role-clarity stemming from weakly constituted (state-based) career structures was linked to a system-wide misunderstanding of AHWs' roles and responsibilities - particularly the cultural components - acting as a barrier to AHWs working to their full capacity for the benefit of patients, broader society and their own professional satisfaction. Conclusions In literature spanning different geographies, service domains and several decades, this review found evidence of complexity in AHWs' accountability relationships that both affects individual and team performance. However, theoretically informed and systematic investigation of accountability relationships and related issues, including the power dynamics that underpin AHW governance and performance in often diverse settings, remains limited and more work in this area is required.